The Internet weather : balancing continuous change and constant truths - Moore, James W. (James Wendell), 1938- (John Wiley & Sons, 2002)
"What will work be like in the future? Futurists often try to answer this question by looking at the effects of the Internet and technology, examining how they have changed our personal and professional lives." "In The Internet Weather, instead of studying all the changes occurring in our world, James Moore looks at all the things that will stay the same. Technology may lead us to more rapid communication, more voluminous information, and a world without the privacy we've come to expect, but it will also force us to think in new ways about old values. Most likely, argues Moore, we will not abandon age-old ideals for new ones, but reorganize human society around the same old ideals we've always held, accommodating and incorporating new technologies into new ways of living under the same, long-held beliefs."--BOOK JACKET.